Tensile Bond Strength and Retention of Three Types of Ceramic Endocrowns - Anahita Fayyazi; Leila Habibi; Bijan Heidari; Sara Tavakolizadeh (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: By development of adhesive dentistry and noble mechanical strength of ceramics, reconstruction of posterior teeth with partial coverage restorations such as ceramic endocrowns is possible. Different ceramics may show different mechanical properties which should be investigated. Purpose: The aim of this experimental in vitro study was to compare the tensile bond strength of endocrowns made by CAD-CAM using 3 types of ceramics. Materials and Method: In this in vitro study, 30 fresh extracted human molars were prepared to evaluate the tensile bond strength of endocrowns made by IPS e.max CAD, Vita Suprinity, and Vita Enamic blocks (n=10). The specimens were mounted and endodontically treated. Standard preparations were done with 4.5±0.5 mm intracoronal extensions into the pulp chamber and the restorations were designed and milled by CAD-CAM technique. All specimens were cemented with a dual polymerizing resin cement according to the manufacturer's instructions. The specimens were incubated for 24 hours and then thermocycled for 5000 cycles at 5-55°C and underwent the tensile strength test by universal testing machine (UTM). Shapiro-Wilk and one-way ANOVA test were used to statistically analyzed (α= 0.05). Results: The highest tensile bond strength values were achieved in IPS e.max CAD (216.39 ±22.67N) and Vita Enamic (216.22±17.72N) followed by Vita Suprinity (211.54±20.01N). There was no significant statistical difference between retention of endocrowns made by CAD-CAM technique among ceramic blocks (p= 0.832). Conclusion: Within the limitation of this study, there was no significant difference between retention of endocrowns made by IPS e.max CAD, Vita Enamic, and Vita Suprinity as ceramic blocks.